Evaluasi Penyaluran Program Anggaran Dana Desa Di Desa Pamah Kecamatan Tanah Pinam Kabupaten Dairi - Sindi Dea Agustina Ginting; Agung Suharyanto; Beby Masitho Batubara (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2022)
Most of the problems in the village are that there are still many programs that have not been implemented properly and some have. This can be seen from the number of people who are not satisfied with the results of the village apparatus program. Evaluation of program distribution will be part of the strategy in making a better policy. The purpose of the study was to determine the evaluation and obstacles in the distribution of the village fund budget program in Pamah Village, Tanah Pinem District, Dairi Regency. The theory used in analyzing the problem is the theory of program evaluation. The research method used is descriptive qualitative method. Sources of data in this study were village heads, representatives of village officials and representatives of the community. The results of the study indicate that effectiveness has not been running as it should, the adequacy of the deliberation system has been implemented, the implementation has not carried out the appropriate program, the responsibility has been satisfactory and the accuracy has focused on the needs of the community. Regarding the inhibiting factors in the distribution of village fund budget programs, many are due to the low participation of the community in designing a policy in which it is aimed at the interests of the village itself. So it can be concluded that program distribution will be more effective if the community is more active in making new programs based on the results of joint discussions.